Risk factors for late defecation and its association with the outcomes of critically ill patients: a retrospective observational study. Issue 1 (December 2016) - Fukuda, Shinya; Miyauchi, Takashi; Fujita, Motoki; Oda, Yasutaka; Todani, Masaki; Kawamura, Yoshikatsu; Kaneda, Kotaro; Tsuruta, Ryosuke
Abstract Background Late defecation was recently reported to be associated with worse clinical outcomes in critically ill patients. However, more research is needed to examine the causes and clinical significance of late defecation. The objectives of this study were to investigate the risk factors for late defecation and its association with the outcomes of intensive care unit (ICU) patients. Methods Patients in an ICU for ≥7 days between January and December 2011 were retrospectively assessed. Based on the time between admission and the first defecation, they were assigned to early (<6 days;n = 186) or late (≥6 days;n = 96) defecation groups. Changes in clinical variables between admission and ICU day 7 were assessed to investigate the effects of late defecation. The clinical outcomes were ICU mortality, length of ICU stay, and length of mechanical ventilation. Results Late enteral nutrition (odds ratio (OR) 3.42; 95 % confidence interval (CI) 1.88–6.22;P < 0.001), sedatives (OR 3.07; 95 % CI 1.71–5.52;P < 0.001), and surgery (OR 1.86; 95 % CI 1.01–3.42;P = 0.047) were the independent risk factors for late defecation. The median (interquartile) changes in body temperature (0.3 [−0.4 to 1.0] vs 0.7 [0.1 to 1.5] °C;P = 0.004), serum C-reactive protein concentration (1.6 [−0.5 to 6.6] vs 3.5 [0.7 to 8.5] mg/dL;P = 0.035), and Sequential Organ Failure Assessment score (−1 [−2 to 1] vs 0 [−1 to 2];P = 0.008) between admission and ICU day 7 were significantly greater in the late defecation group than in the early defecation group. ICU stay was significantly longer in the late defecation group (12 [9 to 19] vs 16 [10 to 23] days;P = 0.021), whereas ICU mortality and the length of mechanical ventilation were similar in both groups. Conclusions Late enteral nutrition, sedatives, and surgery were independent the risk factors for late defecation in critically ill patients. Late defecation was associated with prolonged ICU stay.